Laser metal deposition repair of stainless steel 316L parts - Cailloux, Thomas (Nanyang Technological University, 2023)
The nuclear and offshore wind industries are of great interest to meet the current challenges of producing carbon-free electrical energy in the context of the global energy and climate crisis. However, the structural materials used in these facilities are exposed to aggressive environments that damage components, limiting their lifespan and requiring their replacement. In the context of a circular economy, repair technologies make it possible to limit these replacements, thus reducing the time and costs associated with plant shutdowns. They also allow for minimizing the mineral resources required for the development of new components, as well as the carbon footprint associated with the manufacturing processes and transportation of the components. The objective of this thesis is to develop a process for the repair of metal parts that meets the following deposition criteria: dense, without cracks, with metallurgical bonding to the substrate, and imperceptible in terms of mechanical behavior and corrosion resistance. This process must ultimately be able to repair the initial defect with a return to the original dimensions without damaging the rest of the part. Laser Metal Deposition (LMD) technology, which is based on additive manufacturing, appears to be a promising way to meet these requirements. The LMD process has demonstrated its ability to repair metal parts while maintaining high deposition density and good mechanical properties. The energy provided by the laser allows the material to be fused without significantly affecting the substrate thermally, thereby avoiding distortion of the repaired part. Finally, the implementation of deposition heads on computer numerical control machines allows the repair process to be automated and to achieve a high level of precision compared to manual repair. The thesis, therefore focused on understanding and optimizing two main steps of the repair process: (i) the pre-machining to remove damaged material and (ii) the laser fused powder deposition to replace the material. An understanding of the synergy between these two steps is also essential to obtain a good quality deposit while machining a minimum volume of damage. For this purpose, a study was conducted to optimize the shape and dimensions of the machined defect. An ellipsoidal pre-machining with an opening angle of 120° and optimized deposition parameters were determined. The influence of substrate preheating, interlayer dwell time, and different post-heat treatments on the repair was also studied. The results have allowed proposing a method to homogenize the characteristics of the repaired parts in terms of microstructure, mechanical properties, and corrosion resistance during the deposition of the material, aiming at the imperceptibility of the repair in the part. This work has also allowed the implementation of all these optimized steps in an additive/subtractive hybrid machine to demonstrate the feasibility and efficiency of this emerging technology. Repair times are thus reduced while maintaining a dense repair and slightly improving mechanical properties.